2011
DOI: 10.12968/denu.2011.38.10.704
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of sialolithiasis in the sublingual gland: a diagnostic dilemma

Abstract: This case describes a 35-year-old female who presented with an incidental finding of sublingual gland sialolithiasis. The clinical presentation, investigations and management as well as the pathology are described. This case highlights the diagnostic dilemma in determining the anatomical position of sialoliths on radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…The incidence of sublingual gland sialolithiasis varies in the literature from 0% to 6.4%. 1-3 Studies from the 1950s and 1960s report a higher incidence of 6.4%, which may be falsely elevated due to confusion with stones in the anterior portion of Wharton’s duct. 1,3 At our tertiary care academic center, we have a 1% incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of sublingual gland sialolithiasis varies in the literature from 0% to 6.4%. 1-3 Studies from the 1950s and 1960s report a higher incidence of 6.4%, which may be falsely elevated due to confusion with stones in the anterior portion of Wharton’s duct. 1,3 At our tertiary care academic center, we have a 1% incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Sialoliths most commonly occur in the submandibular gland, outnumbering the parotid gland by approximately 4:1, while stones occur in the sublingual gland in just 0% to 6.4% of cases. 1-3 Because the sublingual gland is a rare site for sialolithiasis, it may be underdiagnosed and may be mistaken as a Wharton’s duct stone.…”
Section: Introductionmentioning
confidence: 99%
“…7 Clarence P. et al reported an unusual case of sialolithiasis of the sublingual gland presenting in a 35-year-old female. They removed the right sublingual salivary gland, together with the five stones (the largest measuring 7x6x4 mm) 7 . Liao LJ et al studied a case of a 50-year-old male with left sublingual gland sialolithiasis who was treated with excision of the left sublingual gland and the stone via a transoral approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the long run, this pressure will lead to the formation of connective tissue and atrophy of acinar cells [12]. Incomplete obstruction will only cause a decrease of the salivary flow, thus explaining why some salivary stones can be symptomless [25]. Giant sialolithiasis refer to calculi whose dimension exceeds 1.5 cm in any direction or when its weight exceeds 1 g [3].…”
Section: Diagnosismentioning
confidence: 99%